Reliability of Tinnitus Loudness Matches under Procedural Variation - Henry, James A.; Flick, Christopher L.; Gilbert, Alison; Ellingson, Roger M.; Fausti, Stephen A. (Journal of the American Academy of Audiology, 1999)
Repeated tinnitus loudness matches (LMs) were obtained to determine response reliability using a computer-automated technique with two procedural variations, fixed or random step sizes, to increase output level during the initial ascending series of tones at each frequency. Twenty subjects with stable, tonal tinnitus were evaluated with both methods during each of two sessions. Response instructions were displayed on a portable computer, and a pen device was used to make response choices that appeared on the touch-sensitive video monitor. For each method, hearing thresholds and LMs were obtained, with 1-dB resolution, at 1/3-octave frequencies from 1 to 16 kHz. Analyses revealed reliability of LMs to be equivalent between methods. LM data are reported in both dB SPL and dB SL, with the SPL values providing greater reliability both within and between sessions (all r's ≥ .889, p's ≤ .0001).Abbreviations: ANOVA = analysis of variance, LAN = local area network, LM = loudness match
Keywords: Loudness; measurement; reliability; tinnitus